REPOSISI TREN ICT BIDANG KAJIAN TEKNOLOGI PENDIDIKAN - Subkhan, Edi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2011)
Educational technology facing lots of problems of misunderstanding, over expectation and reductionism in Indonesia today. It is caused by the less paradigmatic comprehension of the educational technology scholars, so they are . insist to build the educational technology as a discipline, not only as a field of studies. Secondly, the problems come from the reductionism of the educational technology into information and communication technology (JCT), it had been influenced by the JCT trend in education realm today. Thereby most of the people conceived that educational technology is the JCT itself. Based on those facts, educational technology needs to reorient itself by repositioning the JCT as a part of educational technology, not on the contrary. Then, it is important to re-assert that educational technology shouldnt follow the JCT market pragmatism, but to facilitate the social transformative actions trough improving the learning processes in educational practices.